Oxidative stress parameters in women and men with suicidal thoughts and following a suicide attempt - Lech, Magdalena; Ostrowska, Lucyna; Waszkiewicz, Napoleon; Kułak-Bejda, Agnieszka; Maciejczyk, Mateusz; Witczak-Sawczuk, Katarzyna; Zalewska, Anna; Dańkowska, Karolina; Żendzian-Piotrowska, Małgorzata (Frontiers in Psychiatry, 2024)
Background This study aimed to evaluate oxidative stress parameters in individuals with depression and schizophrenia, considering gender differences, and manifesting suicidal behavior, encompassing thoughts without a tendency to be realized, thoughts with a tendency to be realized, and suicide attempts. Methods From among the patients from Department of Psychiatry 120 individuals were selected who met the inclusion criteria and did not meet the exclusion criteria for the study. In the initial phase of the project, patients eligible for the study underwent the M.I.N.I 7.0.2 questionnaire (Mini International Neuropsychiatric Interview). Subsequently, in the second phase of the research, venous blood samples were collected from the patients for the purpose of conducting biochemical assessments, focusing on oxidative stress parameters. Results The obtained results suggest that redox biomarkers, namely TOS (total oxidation state) and OSI (TOS/TAC ratio), in the blood plasma of women increase in tandem with the severity of suicidal behavior. No notable alterations in SOD (Cu-Zn-superoxide dismutase), GPx (glutathione peroxidase), and GSH (reduced glutathione) concentrations and activity were noted between groups exhibiting suicidal behavior. The observed variations in the concentrations and activity of antioxidant parameters were significant solely in comparison to the control group. Conclusions Redox biomarkers TOS and OSI could prove valuable in diagnosing women at a genuine risk of committing suicide. On the other hand, antioxidant parameters – SOD, GPx, and GSH may be instrumental in identifying patients with suicidal behaviors, without specifying their intensity.